Modern trends towards effectiveness of textbooks for teaching Arabic as a second or foreign language - Osman, Nurulhuda; Sahrir, Muhammad Sabri (2011)
The existence of the phenomenon of varieties in the preparation of textbooks for teaching Arabic as a second or foreign language is regarded as a practical challenge which is faced by educators. This situation needs to be justified by identifying standard principles of preparing textbooks; because they are mainly depended in order to choose the appropriate linguistic, cultural, and educational contents. Therefore, this article aims to identify the psychological, cultural and social development, as it relates to elements of language and education approaches in the textbooks, as well as in the context of technical and technological computer as they affect the effectiveness of these textbooks in view of the evolution of technology software in the present day.